A reflection - Machado, Ana Maria (Ondina - Ondine, 2020)
In a text which is, at the same time, reflective in a subjective tone, but which also seeks to be objective according to critical parameters, the author casts a glance at her own work for children and young people, from the publication of her first stories in 1969 and she examines how the issue of gender is presented. She locates his personal path against the development of children’s and youth literature in her country and seeks to relate it to authors of his generation within the framework of their historical and social circumstances. She analyzes the most constant characteristics of her texts and the possible changes or different aspects of her personal literary creation, along that route, both under her own self-reflexive gaze and according to the critical analysis of academics who wrote about her work and who addressed that aspect . In addition, she comments some specific challenges which she finds in the daily work of writing,with regards to grammatical rules bearing gender marks in the Iberian languages and her search for solutions in creative practice.Keywords: reflection, criticism, Ana Maria Machado’s career, literary genres, gender studies, language.